Burn Patient Perspectives on Disability Weights and the Philosophy of Disability: A Gap in the Literature - Paul Won; Karel-Bart Celie; Cindy Rutter; T. Justin Gillenwater; Haig A. Yenikomshian (MDPI AG, 2023)
Background: Disability-adjusted life years (DALY) have a ubiquitous presence in academic global health, including attempts to understand the global burden of burn injuries. Objective: The present scoping review aimed to examine whether disability weights (DWs) were informed by burn patient perspectives and secondarily to determine whether literature indicates which of the three most common philosophical models of disability best aligns with burn patient experiences. Methods: A review of six databases was conducted and The Critical Appraisal Skills Program (CASP) checklist was utilized. Results: Out of a total of 764 articles, zero studies solicited patient perspectives of DWs. Four articles contained data that could be extrapolated to patient perspectives on disability. All articles utilized semi-structured interviews of burn survivors and reported thematic elements including return to work, self-image, and social integration. Patients reported similar themes that burn injuries were disabling injuries and instrumentally detrimental, with modulation based on the patient's social circumstances. Conclusions: This scoping review highlights a significant gap in literature. First, no studies were found directly investigating burn patient perspectives on burn DWs. Current DWs have been derived from expert opinions with limited input from patients. Second, the limited primary patient data gleaned from this review suggest patients consider their injuries as instrumentally detrimental, which aligns most closely with the welfarist view of disability. More explicit investigations into the philosophical model of disability best aligning with burn patient experiences are needed to ground the health economics of burns in sound theory.